Identification of anti-flaviviral drugs with mosquitocidal and anti-Zika virus activity in Aedes aegypti. - Shengzhang Dong; Seokyoung Kang; George Dimopoulos (Public Library of Science (PLoS), 2019)
Zika virus (ZIKV), an emerging arbovirus belonging to the genus Flavivirus, is transmitted by Aedes mosquitoes. ZIKV infection can cause microcephaly of newborn babies and Guillain-Barré syndrome in adults. Because no licensed vaccine or specific antiviral treatment is available for ZIKV infection, the most commonly used approach to control the spread of ZIKV is suppression of the mosquito vector population. A novel proposed strategy to block arthropod virus (arbovirus) transmission is based on the chemical inhibition of virus infection in mosquitoes. However, only a few drugs and compounds have been tested with such properties. Here we present a comprehensive screen of 55 FDA-approved anti-flaviviral drugs for potential anti-ZIKV and mosquitocidal activity. Four drugs (auranofin, actinomycin D (Act-D), bortezomib and gemcitabine) were toxic to C6/36 cells, and two drugs (5-fluorouracil and mycophenolic acid (MPA)) significantly reduced ZIKV production in C6/36 cells at 2 μM and 0.5 μM, respectively. Three drugs (Act-D, cyclosporin A, ivermectin) exhibited a strong adulticidal activity, and six drugs (U18666A, retinoic acid p-hydroxyanilide (4-HPR), clotrimazole, bortezomib, MPA, imatinib mesylate) significantly suppressed ZIKV infection in mosquito midguts. Some of these FDA-approved drugs may have potential for use for the development of ZIKV transmission-blocking strategies.